Improving Packer Machine Operators’ Working Methods Considering REBA, RWL, and CTDs Analysis - M. Yani Syafei; Alfita Intan Putri PD (JIE Scientific Journal on Research and Application of Industrial System, 2017)
To support the production activities to maintain a good production activity, the company should concern on the operators’ health and productivity by providing proper working condition and tools considering the ergonomics aspects. This observation was conducted for operators in handling Bobbin Film Pack materials manually in cigarette company. The problem solving is analyzed by assessment of REBA, RWL, and CTDs. After analyzing the current working posture and lifting method from all of the chosen operators, the root causes were found. The result shows the bad working conditions which are the incorrect working methods and tools. The proposed improvements are used to provide better working condition, which are the new design of materials pallet that suitable with the ergonomics aspects.